Governing Gender Equality Policy - Elomäki, Anna. author. (orcid)0000-0002-1114-1883 Link aut Link
XVII, 201 p. 4 illus.
Keywords: Not as noisy as populist anti-gender campaigns, neoliberal policy regimes pose an equally significant challenge for gender equality projects. Anna Elomäki and Hanna Ylöstalo are incisive in showing how economic policy, strategic management frameworks and an 'evidence hierarchy' constrain feminist claims but also provide footholds. A must-read book for gender equality advocates, practitioners and scholars in the neo-liberal world far beyond Finland. Marian Sawer, Emeritus Professor, Australian National University, Australia This rich theoretically driven book retraces state transformations within Finland and shows in excellent empirical case studies how gender actors and practitioners try to keep the balance between feminist knowledge and specific gender policy implementation. Elomäki and Ylöstalo show how neoliberal governance reforms are deeply gendered and shift the meaning of gender equality to suit the purpose of state reform. A must read for anyone interested or involved in gendered state policy and economic governance! Stefanie Wöhl, Professor of Politics, UAS BFI Vienna, Austria This book analyses the effects of public governance reforms on gender equality policy in Finland. Recent economic crises, rising austerity and increasing opposition to gender equality have led to the defunding of gender equality bodies, and the side-lining of gender equality as a political goal. This policy backlash has taken place alongside transformations to the state and governance, that have changed the discourses, knowledge, actors, and practices of gender equality policy. This book contributes to these discussions by demonstrating the subtleties of the constantly changing governance reform agendas, their operation in practice, and how they intertwine with other elements of the gender equality policy backlash. It is based on more than 100 interviews withcivil servants, politicians, non-governmental organisations, social partners, and think tanks, and a broad range of policy documents and media material. It will appeal to students and scholars of gender studies, public policy and governance. Anna Elomäki is Academy Research Fellow at Tampere University, Finland. Her research interests include economic policies and governance, EU politics and gender equality policy. Hanna Ylöstalo is Senior Lecturer in Sociology at the University of Turku, Finland. Her research interests include knowledge-policy relations, welfare state reform and gender equality policy. .